Parental influence on adolescent adherence to physical-sport practice (Influencia parental de la adherencia de práctica físico-deportiva en adolescentes) - Sanz-Arazuri, Eva; Ponce-De-León-Elizondo, Ana; Valdemoros-San-Emeterio, María Ángeles; Baena-Extremera, Antonio (Retos, 2018)
The aims of this paper were: a) to verify whether the importance granted by parents to leisure physical activity (PA), parental PA, and the parents’ educational level enhance or weaken adherence to PA in their physically active children and, b) to explain the possible interference of such parental factors on adolescents’ adherence to PA. Participants were 1978 children, aged 12 to 16 years. A quantitative and qualitative triangulation technique was employed, using a questionnaire (MACOFYD) and four discussion groups. Descriptive, bivariate, and multinomial regression analyses were employed. Conclusions: it is essential for parents not only to grant considerable importance to PA but also to let their children know about their appraisal. The fact that parents grant more importance to other issues, such as studies, than to motor activity does not reduce the likelihood of their children’s consolidating their PA. Resumen. El objetivo de este trabajo es: a) comprobar si la importancia otorgada a la actividad física (AF) de ocio por los padres, la AF de estos, y su nivel educativo tiene un impacto en la consolidación o debilitamiento de la adherencia de la AF en sus hijos, b) explicar cómo y en qué medida estos factores interfieren con la adhesión de los adolescentes a la AF. La muestra fue de 1978 niños entre 12 y 16 años. Se utilizó una técnica de triangulación cuantitativa y cualitativa, mediante un cuestionario (MACOFYD) y cuatro grupos de discusión. Se realizó un análisis descriptivo, bivariado y de regresión multinomial. Se concluye que es esencial que tanto padres como hijos otorguen bastante importancia a esta práctica; el hecho de que los padres otorguen más importancia a otros temas, como los estudios, no reduce la probabilidad de que los hijos se adhieran y consoliden su AF.